Researching Education : Data, methods and theory in educational enquiry. - Scott, David (Continuum International Pub. Group, 2010)
Researching Education looks at the theory and practice of researching education and examines the philosophical, historical, political and social contexts of research and the implications of these for the collection and analysis of data. Scott and Usher argue that while power is ever present in the construction of research texts, this is inevitable as research imposes a closure of the world through representations and thus is always and inevitably involved with and implicated in the operation of power.¨The authors provideä theoretical framework against previously compiled research c.